The Influence of Gadget Screen Time on the Emotional Development of Early Childhood at SPS Tastbitul Fuad - Astuti, Rahayu Fuji; Watini, Sri; Rista, Nadia (Bulletin of Early Childhood, 2025)
This study explores the impact of gadget screen time on the emotional development of young children at SPS Tastbitul Fuad. Employing a quantitative approach supported by observation and questionnaires, the research investigates how the duration and intensity of screen use influence children's emotional well-being. The findings reveal that screen time has a noticeable effect on emotional development, as prolonged or unregulated use may lead to reduced empathy, irritability, and difficulty managing emotions. Nevertheless, the influence of screen time alone is relatively limited. Emotional growth in early childhood is shaped more substantially by environmental factors, such as parenting styles, the quality of communication between parents and children, and opportunities for social interaction with peers. These aspects are more crucial in helping children recognize, express, and regulate their emotions appropriately. Therefore, while screen time contributes to emotional changes, it should be managed carefully and balanced with positive interactions and guidance from parents and teachers to support healthy emotional development in young children.